AI-Augmented Decision-Making in Management Using Quantum Networks - Mullangi, Kishore; Dhameliya, Niravkumar; Anumandla, Sunil Kumar Reddy; Yarlagadda, Vamsi Krishna; Sachani, Dipakkumar Kanubhai; Vennapusa, Sai Charan Reddy; Maddula, Sai Sirisha; Patel, Bhavik (Asian Business Review, 2023)
Combining artificial intelligence (AI) and quantum networks can revolutionize management decision-making. This study delves into the implications of AI-augmented decision-making using quantum networks, focusing on its primary objectives, methodology, significant findings, and policy implications. By thoroughly examining the latest research, analyzing case studies, and exploring future possibilities, this study investigates the potential of combining AI and quantum computing to improve strategic decision-making, streamline operations, and foster innovation in management. The methodology entails thoroughly analyzing existing literature, carefully examining real-world case studies and a forward-looking forecast of future trends in AI-quantum integration. Significant discoveries emphasize the remarkable computational power and efficiency, enhanced decision-making abilities, and the potential for groundbreaking innovation and disruption that AI-augmented decision-making using quantum networks brings. Nevertheless, the study highlights various constraints and policy implications that need to be considered, such as technical hurdles, ethical concerns, and regulatory structures, to guarantee a responsible and ethical implementation. This study enhances our understanding of the potential impact of AI-augmented decision-making in management, particularly when combined with quantum networks. It emphasizes the need for proactive policy measures to ensure that the benefits of this technology are maximized while risks are minimized.